Measurement of b hadron lifetimes in pp collisions at √s=8TeV - KAYA, MİTHAT (My University, 2018)
© 2018, CERN for the benefit of the CMS collaboration.Measurements are presented of the lifetimes of the B 0, Bs0, Λb0, and Bc+ hadrons using the decay channels B0→J/ψK∗(892)0, B0→J/ψKS0, Bs0→J/ψπ+π-, Bs0→J/ψϕ(1020), Λb0→J/ψΛ0, and Bc+→J/ψπ+. The data sample, corresponding to an integrated luminosity of 19.7fb-1, was collected by the CMS detector at the LHC in proton–proton collisions at s=8TeV. The B 0 lifetime is measured to be 453.0±1.6(stat)±1.8(syst)μm in J / ψK ∗(892) 0and 457.8±2.7(stat)±2.8(syst)μm in J/ψKS0, which results in a combined measurement of cτB0=454.1±1.4(stat)±1.7(syst)μm. The effective lifetime of the Bs0 meson is measured in two decay modes, with contributions from different amounts of the heavy and light eigenstates. This results in two different measured lifetimes: cτBs0→J/ψπ+π-=502.7±10.2(stat)±3.4(syst)μm and cτBs0→J/ψϕ(1020)=443.9±2.0(stat)±1.5(syst)μm. The Λb0 lifetime is found to be 442.9±8.2(stat)±2.8(syst)μm. The precision from each of these channels is as good as or better than previous measurements. The Bc+ lifetime, measured with respect to the B + to reduce the systematic uncertainty, is 162.3±7.8(stat)±4.2(syst)±0.1(τB+)μm. All results are in agreement with current world-average values.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Astronomy and Astrophysics; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; SPACE SCIENCE; ASTRONOMY & ASTROPHYSICS; Mühendislik (çeşitli); Fizik Bilimleri; Fizik ve Astronomi (çeşitli); Engineering (miscellaneous); Physical Sciences; Physics and Astronomy (miscellaneous)